2017
DOI: 10.5811/westjem.2017.4.33411
|View full text |Cite
|
Sign up to set email alerts
|

Managing Acute Behavioural Disturbances in the Emergency Department Using the Environment, Policies and Practices: A Systematic Review

Abstract: IntroductionEffective strategies for managing acute behavioural disturbances (ABDs) within emergency departments (EDs) are needed given their rising occurrence and negative impact on safety, psychological wellbeing, and staff turnover. Non-pharmacological interventions for ABD management generally fall into four categories: environmental modifications; policies; practice changes; and education. Our objective was to systematically review the efficacy of strategies for ABD management within EDs that involved cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 27 publications
0
57
0
1
Order By: Relevance
“…Our recent systematic review of any literature on chemical restraint published since 1996 identified 33 potentially relevant systematic reviews (SRs) of primary studies (Muir‐Cochrane et al ). Only nine SRs included primary papers, which all specifically noted that medications had been administered without consent (Aguilera‐Serrano et al ; Goulet et al ; Jarrett et al ; Laiho et al ; Luciano et al ; Newton‐Howes & Mullen ; Steinert et al ; Tingleff et al ; Weiland et al ). None of these SRs reported on the effectiveness of medications.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent systematic review of any literature on chemical restraint published since 1996 identified 33 potentially relevant systematic reviews (SRs) of primary studies (Muir‐Cochrane et al ). Only nine SRs included primary papers, which all specifically noted that medications had been administered without consent (Aguilera‐Serrano et al ; Goulet et al ; Jarrett et al ; Laiho et al ; Luciano et al ; Newton‐Howes & Mullen ; Steinert et al ; Tingleff et al ; Weiland et al ). None of these SRs reported on the effectiveness of medications.…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates, 321 were manually screened, and 286 records were excluded for title and abstract. We reviewed the full text of 35 studies, 24 of which were excluded [11,12,14,18,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Finally, eleven SRs were included in the narrative synthesis ( Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Only one of the included systematic reviews performed a metaanalysis [44], heterogeneity due to the design of primary studies, weak methodological rigor, and the lack of standardized tools that assess mental health, and built environments are the main drawbacks reported by the others SRs. Full-text articles excluded, with reasons (n = 22) Did not meet study design (n = 13) [12], [14], [18], [23], [25], [26], [28]- [31], [37], [40] [24] Did not meet study intervention (n = 6) [32], [33], [35], [36], [38], [39] Did not meet study outcome (n = 3) [11], [27], [34] (i) e research looking at the role of the built environment on mental health is relatively new, and causal pathways connecting both constructs are just starting to emerge. According to van den Bosch et al, mental health is consistently influenced directly or indirectly by multiple environmental exposures, and depressive mood may be the result of the rapid urbanization and a disconnection from our evolutionary origin and natural environments [53].…”
Section: Discussionmentioning
confidence: 99%
“…wait-times, lack of privacy), negative attitudes among staff, implementing interpersonal and communication skills training for physicians and nurses, and legislative support for accompanying persons’ involvement in the care of their loved ones in healthcare facilities. Additional approaches have been suggested, although systematic reviews of the impact of potential interventions note the paucity of robust evidence to support any of those studied [ 29 , 30 ]. Clearly, more rigorous research is needed, but we discuss some interesting approaches below.…”
Section: Complex Problems Require Complex Approachesmentioning
confidence: 99%